PERFORMANCE STANDARD OF SPA SERVICES WITH THE JAVANESE MASSAGE METHOD IN THE ACADEMY OF SOCIAL PROSPERITY "AKK" OF YOGYAKARTA (Journal of Technology and Operations Management, 2019)
Spa is a beauty treatment that not only refreshes and calms the mind. But it also has several health benefits. This paper discussed the implementation of Spa services refer to the Operational Service Standards (SOP) which will be the main force. The role of the government through four departments, in collaboration with the Indonesian Spa Association together to form Business Standards, Services, National Work Competency Standards (SKKNI), Curriculum Standardization with the Ministry of Education, and Promotion Cooperation Standards with the Ministry of Tourism. According to the SKKNI employment in the Spa field refers to knowledge, skills, attitudes. The concept of service at Spa refers to excellent service to foster trust in customers. Excellent service must be supported by quality human resources that are reliable, have a vision that is far ahead and can develop strategies and tips for excellent service that has excellence. The Javanese Massage method applies a combination of several body treatments that originate from cultural and technological traditions, with Javanese sorting methods. It is beneficial for the muscles and can be effective in blood circulation, relieving muscle tension, stimulating the rhythmic nerves to achieve a sedative effect, stimulating and calming. In the Spa treatment, there are various body treatments, namely body scrubs, body massages, body masks and aroma therapy.